THE MALAYSIAN JOURNAL OF LIBRARY AND INFORMATION SCIENCE 2001-2006: A BIBLIOMETRIC STUDY - Bakri, Aryati; Willett, Peter (Malaysian Journal of Library and Information Science, 2017)
This paper analyses publication and citation patterns in the Malaysian Journal of Library and Information Science (MJLIS) from 2001-2006, and compares the results with those obtained in an earlier study by Tiew et al. (2002) covering the period 1996-2000. Our results show that the number of publications has increased from the 76 articles in the Tiew study to 85 articles here, with statistically significant changes in the types of article, in the numbers of references per article and in the lengths of the articles. The complete set of 161 articles attracted a total of 87 citations, 52 of which were self-citations, with 14% of the MJLIS articles having been cited at least once.